Avaliaç\~ao dos fundos setoriais: CT-Transporte - Fabiano Mezadre Pompermayer; Erivelton Pires Guedes (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– This Discussion Paper is part of a series of studies on the Sector Funds conducted by Ipea in partnership with the Brazilian Ministry of Science and Technology. The CT-Transporte is, among sector funds, the smallest in number of projects and committed resources. The reason for such poor performance was the contention of the revenue that the DNIT would get from exploring the use of road infrastructure by the telecommunications industry. Without resources, and after the creation of the so called Transversal Actions, the financing of projects, that would originally demand resources from the CT-Transporte, started to occur through these new actions. Still, the provision of financial resources for projects in transportation was lower than the demand. Analyzing the projects financed by other funds, we could identify more than 60 projects that would be within the scope of CT-Transporte (versus just nine by the specific fund), showing the inability of the fund to promote research and technological development in the transportation sector. Corporate participation is low, although it occurred in the bigger projects. Considering only the projects directly funded by the CT-Transporte and by the Transversal Actions for Transportation and Logistics, corporate participation is even lower. The topics studied in the projects that were granted with more projects and also more funding are: Intelligent Transport System (ITS), Transportation and Logistics and Inland Waterways and Transportation. Few projects on issues important to the transportation sector were identified, with several important issues not covered in the projects of the fund.
Keywords: O38; L91; 330